THE MOST IMPORTANT CHARACTER OF KHUVAYDO'S WORK (American Journal of Pedagogical and Educational Research, 2023)
This article explores the poet of Huvaydo, a major representative of mysticism poetry, exploring the thematic wealth, linguistic nuances and emotional power that define his lyrical style. It concludes with reflections on the impact of Huvaydo's lyricism and suggestions for further research.